Core material glass for micro-channel plate as well as preparation method and application of core material glass

Through specific component ratios and process processing, core glass for microchannel plates with transition temperature and softening temperature higher than the requirements was prepared, which solved the problem of insufficient softening temperature of core glass in the prior art, and realized the third generation of microchannel plates The good matching of leather glass improves the performance and quality of the microchannel plate.

CN119461835APending Publication Date: 2025-02-18CHINA BUILDING MATERIALS ACADEMY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411502027.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

现有技术难以制备出与三代微通道板用皮料玻璃相适配的芯料玻璃,芯料玻璃的软化温度低于760℃,导致在拉制和酸液腐蚀过程中可能出现热畸变和微应力,影响微通道板的质量。

Method used

The core glass for microchannel plates with a specific component ratio includes 18 to 24% SiO2, 0 to 16% B2O3, La2O3 and HfO2 contents are 23 to 35%, 10 to 16% BaO, 1 to 4% Al2O3 , 3 to 7% Y2O3 and 5 to 10% Ho2O3, control the ratio of the sum of SiO2 and B2O3 contents to the sum of HfO2 and Ho2O3 contents in the range of 1.5 to 3.5:1, and passes through a specific melting and annealing process, Core glass with a transition temperature Tg≥700℃ and a softening temperature Tf≥760℃ were prepared.

Benefits of technology

The prepared core glass has a high transition temperature and softening temperature, and the thermal expansion coefficient is within the range of 80~85×10-7/K. It is suitable for matching with leather glass for third-generation microchannel plates, which improves the signal noise of microchannel plates. The ratio and resolution are ensured, and the circular shape of the micropores and the integrity of the skeleton are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461835A_ABST
    Figure CN119461835A_ABST
Patent Text Reader

Abstract

The invention relates to core material glass for a micro-channel plate as well as a preparation method and application of the core material glass. The core material glass for the micro-channel plate comprises the following components in percentage by mass of oxides: 18-24% of SiO2; 0 to 16% of B2O3; the sum of the contents of La2O3 and HfO2 is 23 to 35 percent; 10% to 16% of BaO; 1 to 4% of Al2O3; 3 to 7% of Y2O3; and 5 to 10% of Ho2O3. The technical problem to be solved is to provide the core material glass for the microchannel plate, the transition temperature Tg of the core material glass is greater than or equal to 700 DEG C, the softening temperature Tf of the core material glass is greater than or equal to 760 DEG C, and the core material glass is suitable for the third-generation microchannel plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of glass for microchannel plates, and in particular relates to a core glass for microchannel plates and a preparation method and application thereof. Background Art

[0002] Microchannel plates (MCP) are an excellent two-dimensional electron multiplying material with the characteristics of high gain, high spatial resolution, and high temporal resolution. They are the core material for extremely weak photoelectric detection devices such as image intensifiers, photomultiplier tubes, and photon counting tubes. They have a very important application position in high-energy physics, radiation diagnosis and treatment, space detection, low-light night vision, ultraviolet detection, nuclear detection and other fields.

[0003] The core of the current mainstream microchannel plate manufacturing technology is the glass multi-fiber drawing technology. During the preparation process, the skin glass tube that is difficult to dissolve in acid and the matching core glass rod that is soluble in acid are drawn together at high temperature into glass single fiber filaments, and then the glass single fiber filaments are arranged into bundles to form multifilaments. Several multifilaments are bundled again, and the outer cover is wrapped with edge glass. After high-temperature fusion, it is cut into slices, and then the core glass is removed by acid etching to form an MCP microporous array structure. The above-mentioned process determines that the thermal properties, mechanical properties, and chemical compatibility of the core glass and the skin glass must match. At the same time, the core glass and the skin glass must show completely different acid etching capabilities to the same acid solution: the core glass has poor acid corrosion resistance, while the skin glass has strong acid corrosion resistance.

[0004] In order to further improve the signal-to-noise ratio and resolution of MCP, the third-generation MCP leather glass with low noise and high secondary electron emission coefficient has been developed. Compared with the second-generation MCP leather glass, the third-generation MCP leather glass has achieved significant improvements in thermodynamic properties, and its transition temperature and softening temperature have been significantly improved. Among them, its transition temperature (T g ) reaches above 620℃, and the softening temperature reaches 680℃ (T f ) and above, the thermodynamic expansion coefficient is 65×10 -7 / K or above. According to the thermodynamic adaptation principle of MCP core glass, it is adapted to the transition temperature T of the core glass used in the third generation MCP. g Should be ≥700℃, softening temperature T f The temperature should be ≥760℃ and the coefficient of thermodynamic expansion should be ≥80×10 -7 / K.

[0005] However, the optimal softening temperature T of the core glass prepared by the prior art is f≥680℃, and its softening temperature is lower than 760℃. In the process of preparing MCP, if the softening temperature of the core glass is low, thermal distortion or micro stress may be generated during the multifilament drawing and high-temperature melting and pressing process, and these micro stresses will be instantly amplified during the subsequent acid corrosion of the core glass, accelerating the deformation of the MCP substrate bracket. Therefore, the preparation of core glass compatible with the third-generation MCP skin glass is a hot topic in this field. Summary of the invention

[0006] The main purpose of the present invention is to provide a core glass for a microchannel plate and a preparation method and application thereof. The technical problem to be solved is how to provide a core glass for a microchannel plate with a transition temperature T g ≥700℃, softening temperature T f ≥760℃, suitable for leather glass for third-generation microchannel plates.

[0007] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. According to the core glass for a microchannel plate proposed by the present invention, in terms of oxide mass percentage, it includes: 18-24% SiO2; 0-16% B2O3; the sum of La2O3 and HfO2 is 23-35%; 10-16% BaO; 1-4% Al2O3; 3-7% Y2O3; 5-10% Ho2O3; the sum of the contents of SiO2 and B2O3 is m1; the sum of the contents of HfO2 and Ho2O3 is m2; m1:m2 is 1.5-3.5:1.

[0008] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0009] Preferably, the core glass for the aforementioned microchannel plate, wherein the mass ratio of the La2O3 to the HfO2 is 3 to 6:1.

[0010] Preferably, the aforementioned core glass for the microchannel plate further comprises a clarifier, wherein the clarifier is at least one of Sb2O3 and As2O3.

[0011] Preferably, in the aforementioned core glass for the microchannel plate, the clarifier is 0.1-0.3%.

[0012] Preferably, the core glass of the aforementioned microchannel plate has a transition temperature T g ≥700℃; softening temperature T f ≥760℃; thermal expansion coefficient at 20~300℃ is 80×10 -7 / K~85×10 -7 / K.

[0013] The purpose of the present invention and the technical problem solved by the present invention are also achieved by adopting the following technical solutions. According to the method for preparing the core glass for the microchannel plate proposed by the present invention, the method comprises the following steps:

[0014] S1: The raw materials are mixed uniformly to form a batch material; the batch material comprises, in terms of oxide mass percentage, 18-24% SiO2; 0-16% B2O3; the sum of La2O3 and HfO2 is 23-35%; 10-16% BaO; 1-4% Al2O3; 3-7% Y2O3; 5-10% Ho2O3; the sum of the contents of SiO2 and B2O3 is m1; the sum of the contents of HfO2 and Ho2O3 is m2; m1:m2 is 1.5-3.5:1;

[0015] S2: Melting, clarifying and homogenizing the batch material prepared in S1 to obtain glass liquid;

[0016] S3: Cooling the glass liquid homogenized in S2 to 1300-1400°C, and then performing casting, rough annealing, and precision annealing in sequence to obtain a core glass rod;

[0017] S4: Optically grind and polish the core glass rod prepared in S3.

[0018] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0019] Preferably, in the aforementioned preparation method, the S2 melting temperature is 1400-1550°C, and the melting time is 6-8h.

[0020] Preferably, in the aforementioned preparation method, during the rough annealing process, the annealing temperature is kept at 600-700° C. for 3-6 hours.

[0021] Preferably, in the aforementioned preparation method, the precision annealing comprises: heating to 550-650°C at 2.5-4.0°C / min, keeping the temperature for 3-5 hours, and then cooling to room temperature at 0.5-1.5°C / h.

[0022] The purpose of the present invention and the technical problem to be solved are also achieved by the following technical solutions. According to a microchannel plate proposed by the present invention, the core glass is made by the above technical solution, and the skin glass transition temperature T g ≥620℃, softening temperature T f ≥680℃, thermal expansion coefficient of 20~300℃ is 70×10 -7 / K~75×10 -7 / K.

[0023] By means of the above technical solution, the core glass for a microchannel plate and the preparation method and application thereof proposed in the present invention have at least the following advantages:

[0024] 1. The present invention provides a core glass for a microchannel plate and a preparation method thereof. By selecting specific components and adjusting the ratio between the components, the core glass has a strong network skeleton and a transition temperature T g ≥700℃, softening temperature T f ≥760℃, thermal expansion coefficient 80~85×10 -7 / K; more compatible with the third generation leather glass.

[0025] 2. A core glass for a microchannel plate and a preparation method thereof provided by the present invention, wherein the mass ratio of La2O3 to HfO2 is controlled to be 3 to 6:1, and the acid dissolution rate of the core glass sample is tested using 10% hydrochloric acid at 60°C, and the acid dissolution rate is ≥10mg / (cm 2 ×min); and the glass has good anti-crystallization performance.

[0026] 3. The present invention also provides a microchannel plate, which comprises a core glass and a skin glass, wherein the core glass transition temperature T g ≥700℃, softening temperature T f ≥760℃, and expansion coefficient matching leather glass 80~85×10 -7 / K, leather glass transition temperature T g ≥620℃, softening temperature T f ≥680℃, thermal expansion coefficient at 20~300℃ is 70~75×10 -7 / K, the skeleton of the finally obtained microchannel plate is intact and the micropores maintain a circular shape.

[0027] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A physical picture of a microchannel plate microporous structure array prepared from the glass material of Example 1;

[0029] Figure 2 This is a physical picture of the microchannel plate microporous structure array made of glass material in Comparative Example 1. DETAILED DESCRIPTION

[0030] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the following is a detailed description of a core glass for a microchannel plate and a preparation method thereof and its specific implementation method, structure, characteristics and effects of the application thereof proposed in accordance with the present invention, in combination with the accompanying drawings and preferred embodiments.

[0031] Generally, the core glass for microchannel plates is mainly composed of: glass skeleton structure oxides; easily acid-soluble oxides; network external oxides for adjusting viscosity, thermal and chemical stability, and improving material properties. The components in the glass interact with each other and jointly determine the various properties of the glass. Therefore, in order to significantly improve the transition temperature and softening temperature of the core glass and make it compatible with the high softening temperature skin glass used in the third-generation MCP, the present application dopes oxides with high softening points such as HfO2 and Ho2O3 in the glass component. However, the inventors found that in order to maintain the basic acid etching performance and thermal and chemical stability of the core glass, the amount of oxides with high softening points doped in the glass component should be kept in a certain ratio with the easily acid-soluble oxide La2O3; the inventors further found that the material components forming the glass skeleton structure and the doped high softening point oxides, that is, the sum of the masses of SiO2 and B2O3 in the present invention, m1, H f The sum of the masses of O2 and Ho2O3, m2, strictly controls the ratio of m1 to m2 within a certain range, which is beneficial to improving the anti-crystallization performance of the core glass, and improving the stability and weather resistance of the glass. On the basis of the above, the content of the oxides in the glass skeleton structure and other network external oxides is appropriately adjusted so that the various properties of the obtained core glass are suitable for the skin glass for the third generation MCP. The technical solution of the present invention is formed based on this inventive concept.

[0032] The following is an explanation of the range of each component (ingredient) of the glass material of the present invention. In the present invention, unless otherwise specified, the content of each component and the total content are all expressed in mass percentage, i.e., the content of each component and the total content are the mass percentage of the total amount of the glass material converted into oxide composition.

[0033] The present invention proposes a core glass for a microchannel plate, which includes, by oxide mass percentage, 18-24% SiO2; 0-16% B2O3; the sum of La2O3 and HfO2 is 23-35%; 10-16% BaO; 1-4% Al2O3; 3-7% Y2O3; 5-10% Ho2O3; the sum of the contents of SiO2 and B2O3 is m1; the sum of the contents of HfO2 and Ho2O3 is m2; and m1:m2 is 1.5-3.5:1.

[0034] The SiO2 is an important component for forming the basic skeleton structure of the core glass. The present invention strictly limits the mass percentage of SiO2 in the glass to 18-24% to maintain the strength and chemical stability of the glass, the viscosity of the glass, the thermal expansion coefficient and other properties. If the mass percentage of SiO2 in the glass is lower than 18%, the chemical stability of the glass will be deteriorated; and if the mass percentage of SiO2 in the glass is higher than 24%, the viscosity of the glass will increase, the expansion coefficient will be too low, and the core glass will not be able to match the skin glass for the third generation MCP.

[0035] B2O3 is a glass-forming oxide and the main component that forms the basic skeleton in the glass structure. The present invention preferably limits its mass percentage in the core glass to 10-16%. If its mass percentage in the core glass is less than 10%, the acid dissolution rate of the core glass will be significantly reduced, and then the acid etching process will be difficult in the subsequent MCP preparation process; if its mass percentage in the core glass exceeds 16%, the viscosity of the core glass will be significantly reduced, which will deteriorate its compatibility with the skin glass for the third-generation MCP.

[0036] La2O3 and HfO2 are core glass structure regulating oxides. Properly increasing their components in the core glass system can increase the softening temperature of the core glass; and they are also the main oxides for regulating the acid dissolution rate of glass. The present invention preferably limits the sum of the mass percentages of the two in the core glass to 23-35%. When the total mass percentage of La2O3 and HfO2 in the core glass exceeds 35%, the chemical stability and structural stability of the core glass will be reduced, and the anti-crystallization ability of the core glass will also be significantly reduced; when the total mass percentage of La2O3 and HfO2 in the core glass is less than 23%, the acid dissolution rate of the core glass will be significantly reduced. Preferably, in some embodiments, the present invention strictly limits the mass ratio of La2O3 and HfO2 in the core glass to 3-6:1 to ensure the maintenance of the basic acid etching performance and thermal and chemical stability of the glass. The reason is that excessive addition of HfO2 will deteriorate the glass-forming performance, leading to ceramicization of the core glass, which is not conducive to the stability of the core glass.

[0037] BaO is an oxide outside the glass network and also a flux for the glass. Its mass percentage in the core glass is strictly limited to 10-16%, which can maintain the acid dissolution rate of the core glass, improve the material properties of the glass molding, and is beneficial to the molding operation and thermal processing performance of the glass; however, if its content exceeds the maximum value of this range, the chemical stability of the glass will deteriorate, leading to phase separation of the glass; if its content is lower than the minimum value of this range, the acid dissolution rate of the core glass will be reduced.

[0038] Al2O3 is a core glass structure regulating oxide, and its mass percentage in the core glass will affect the thermal expansion coefficient and acid dissolution rate of the core glass; if its mass percentage in the core glass is higher than 4%, it will lead to enhanced glass network bonding and greatly reduced acid dissolution rate, making the MCP acid etching process more difficult and difficult to form through holes; however, if its mass percentage in the core glass is lower than 1%, the chemical stability and thermal stability of the core glass will be reduced.

[0039] Y2O3 is an oxide outside the glass network. The present invention preferably limits its mass percentage in the core glass to 3-7%. Under this condition, the core glass has suitable high-temperature viscosity and softening temperature. However, if too much is added, the glass-forming properties of the glass will deteriorate and phase separation will occur.

[0040] Ho2O3 is an oxide outside the glass network. The mass percentage of Ho2O3 in the core glass is 5-10%, which can significantly increase its transition temperature and softening temperature, making the core glass better compatible with the skin glass for the third-generation MCP. However, when its mass percentage in the core glass is higher than 10%, it will increase the melting difficulty and glass-forming properties of the core glass.

[0041] The sum of the mass percentages of SiO2 and B2O3 in the core glass is recorded as m1, the sum of the mass percentages of Ho2O3 and HfO2 in the core glass is recorded as m2, and the ratio of m1 to m2 is 1.5-3.5:1; under this condition, the anti-crystallization performance of the core glass can be prevented from being reduced, and the thermal expansion coefficient of the glass can be prevented from being difficult to meet the design requirements.

[0042] Preferably, in the above technical solution, the core glass further includes a clarifier, and the clarifier is at least one of Sb2O3 and As2O3. In some embodiments, the content of the clarifier is 0.1-0.3%. The present invention adds a clarifier to the glass component in order to facilitate the clarification and homogenization of the glass liquid during the preparation process, and strictly limits the content of the clarifier so that the core glass can meet the preset requirements of various properties.

[0043] The present invention adopts the above technical solution, and the obtained core glass has the following characteristics:

[0044] Its glass transition temperature T g ≥700℃; softening temperature T f ≥760℃; thermal expansion coefficient at 20~300℃ is (80~85)×10 -7 / K.

[0045] The present invention also provides a method for preparing a core glass for a microchannel plate, which comprises the following steps:

[0046] Preparation of S1 batch material: Calculated in terms of oxide mass percentage, the batch material includes: 18-24% SiO2; 0-16% B2O3; the sum of La2O3 and HfO2 contents is 23-35%; 10-16% BaO; 1-4% Al2O3; 3-7% Y2O3; 5-10% Ho2O3; the sum of the contents of SiO2 and B2O3 is m1; the sum of the contents of HfO2 and Ho2O3 is m2; m1:m2 is 1.5-3.5:1.

[0047] Preferably, in some embodiments, a clarifier is added to promote clarification and homogenization of the glass liquid. In some embodiments, the clarifier is at least one of Sb2O3 and As2O3; further preferably, the mass percentage of the clarifier in the batch is 0.1-0.3%. The amount of the clarifier is strictly limited to ensure that the various properties of the prepared glass meet the expectations.

[0048] S2 melting, clarifying and homogenizing: adding the batch material prepared in S1 into the crucible, melting, clarifying and homogenizing.

[0049] In some embodiments, when the amount of batch material is too large, the batch material is added to the crucible in multiple times, and the batch material is added only after the added batch material is melted, with the interval between each addition being about 1 hour.

[0050] Preferably, in some embodiments, the melting temperature is 1400-1550°C, and the melting time is 6-8h. The temperature and time of high-temperature melting are limited to a reasonable range. On the premise of ensuring that the batch material is melted by high-temperature heating to completely melt the raw materials, the lowest possible melting temperature and the shortest melting time are used to improve efficiency. During the melting, clarifying and homogenizing process, a stirring rod is used to stir continuously.

[0051] The crucible and the stirring rod need to be corrosion-resistant to avoid being corroded by the glass liquid and affecting the performance of the glass. In some embodiments, a pure platinum (Pt) crucible is used; in other embodiments, a platinum alloy is used, such as a platinum-tungsten alloy (the mass percentage of tungsten in the alloy is ≤5%), a platinum-ytterbium alloy (the mass percentage of ytterbium in the alloy is ≤5%).

[0052] S3 molding and annealing: After cooling the glass liquid obtained by S2 to 1300-1400°C, it is poured into a mold for molding. After the pouring is completed, rough annealing and precision annealing are performed in sequence to form a core glass rod. The present invention adopts a technical scheme of rough annealing first and then precision annealing, which is conducive to releasing the internal stress of the prepared core glass, avoiding the reduction of the mechanical strength of the MCP due to the release of the internal stress of the glass material during the preparation of the MCP, making it easy to break, and affecting the service life and reliability of the microchannel plate; at the same time, through this annealing scheme, its electrical performance can be guaranteed to be stable, thereby improving the stability and accuracy of the microchannel plate.

[0053] In some embodiments, after pouring is completed, rough annealing is performed at an annealing furnace temperature of 600-700°C for 3-6 hours; preferably, in some embodiments, the annealing furnace temperature is 630-680°C, and the insulation time is 3-5 hours; further preferably, in other embodiments, the annealing furnace temperature is 630-660°C, and the insulation time is 3-4 hours.

[0054] In some embodiments, the core glass is subjected to precision annealing, and the heating rate is 2.5-4.0°C / min, from room temperature to 550-650°C, then kept at this temperature for 3-5 hours, and then cooled to room temperature at 0.5-1.5°C / h. Preferably, in other embodiments, the core glass is subjected to precision annealing, and the heating rate is 2.5-4.0°C / min, from room temperature to 580-620°C, then kept at this temperature for 3.5-4.5 hours, and then cooled to room temperature at 0.5-1.5°C / h. In some embodiments, the room temperature is 25±1°C.

[0055] The present invention strictly limits the process parameters of rough annealing and precision annealing, which is beneficial to better eliminate the stress in the glass and improve the mechanical strength of the glass; it is also beneficial to avoid the problems of edge cracking and edge collapse caused by the release of internal stress of the core glass during the preparation of MCP.

[0056] S4 finished product preparation: The core glass rod prepared in S3 is subjected to optical grinding, polishing and other processing steps to obtain a finished core glass for preparing MCP.

[0057] The present invention also provides a microchannel plate, which comprises a skin glass and a core glass, wherein the core glass is made of the core glass of the aforementioned technical solution; the skin glass has a transition temperature T g ≥620℃, softening temperature T f ≥680℃, thermal expansion coefficient of 20~300℃ is 70×10 -7 / K~75×10 -7 / K.

[0058] In some embodiments, the components of the leather glass, calculated by the mass percentage of oxides, include: 20-30% PbO, 40-45% SiO2, 18-25% BaO, 1-5% Cs2O, 0.5-5% MgO, 0.5-5% CaO, 0.5-5% Al2O3, and 0-3% Rb2O.

[0059] The microchannel plate prepared by the present invention has good compatibility between the skin material glass and the core material glass, the skeleton of the prepared microchannel plate is intact, and the micropores maintain a circular shape.

[0060] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0061] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0062] In this embodiment and comparative example, the raw material corresponding to Al2O3 is aluminum hydroxide or aluminum oxide; the other raw materials for each functional component can be each oxide itself, or the corresponding carbonate or nitrate. For example, the raw material corresponding to the functional component SiO2 can be silicon dioxide, and the raw material corresponding to BaO can be barium carbonate or barium nitrate.

[0063] The testing methods of various performance indicators in the embodiments of the present invention and the comparative examples are as follows:

[0064] Transition temperature T g And softening temperature T f Test: According to GB / T 7962.16-2010 colorless optical glass test method;

[0065] Thermal expansion coefficient test: Tested in accordance with GB / T 7962.16-2010 colorless optical glass test method;

[0066] Anti-crystallization test: observe and test the crystallization and phase separation of the core glass at 750-1100℃;

[0067] Acid dissolution rate test: The core glass sample was subjected to an acid dissolution rate test using 10% hydrochloric acid at 60°C.

[0068] Example 1

[0069] This embodiment prepares a core glass for a microchannel plate, comprising the following steps:

[0070] S1: Weigh raw materials according to the glass component ratio in Table 1, and mix them evenly to obtain a batch material.

[0071] S2: Add the batch material prepared in S1 into a Pt crucible several times, melt and clarify at 1500℃ to homogenize, and use a Pt stirring rod to stir continuously during the melting and clarifying process;

[0072] S3: The glass liquid obtained after homogenization of S2 is cooled to 1300°C, and then poured into a mold for forming. After pouring, it is roughly annealed in an annealing furnace at 650°C for 4 hours, and then cooled with the furnace; after rough annealing, it is finely annealed again at a heating rate of 3.0°C / min, heated to 600°C, and then kept for 4 hours, and then cooled to room temperature at 1.0°C / h to obtain a core glass rod;

[0073] S4: The core glass rod obtained by the process of S3 is subjected to optical grinding and polishing to obtain a finished core glass rod for preparing MCP.

[0074] The core glass rod prepared above is subjected to a transformation temperature T g , softening temperature T f , thermal expansion coefficient, anti-crystallization ability, acid dissolution rate test. The test data are shown in Table 5.

[0075] Preparation of MCP. The core glass rod prepared above is embedded with the third-generation MCP skin glass, wherein the components of the third-generation MCP skin glass are calculated by oxide mass percentage: 25.9% PbO, 42.8% SiO2, 21.0% BaO, 4.7% Cs2O, 1.6% MgO, 2.1% CaO, 1.7% Al2O3, 0.2% Rb2O; the transition temperature (T g ) reaches above 620℃, and the softening temperature reaches 680℃ (T f ) or more. After the single wire and multi-wire are drawn, the multi-wire is regularly arranged and melted into a blank plate section, and then sliced, ground and polished to obtain a blank plate. The blank plate is acid-corroded, hydrogen-reduced, and electrode-plated to obtain a solid edge-wrapped microchannel plate. The actual picture of the prepared microchannel plate microporous structure array is as follows Figure 1 As shown, the micropore shape of the prepared MCP after acid etching was observed and recorded.

[0076] Example 2

[0077] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0078] Example 3

[0079] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0080] Example 4

[0081] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0082] Example 5

[0083] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0084] Example 6

[0085] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0086] Example 7

[0087] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0088] Example 8

[0089] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0090] Example 9

[0091] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0092] Example 10

[0093] The difference between this embodiment and embodiment 1 is that the process parameters of this embodiment are as shown in Table 2, the remaining steps are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0094] Embodiment 11

[0095] The difference between this embodiment and embodiment 1 is that the process parameters of this embodiment are as shown in Table 2, the remaining steps are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0096] Example 12

[0097] The difference between this embodiment and embodiment 1 is that the composition ratio of each component in the raw material of this embodiment is as shown in Table 1, and the content ratio of La2O3 to HfO2 is 1.9:1, which is significantly lower than the content ratio of La2O3 to HfO2 in embodiment 1. The remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0098] Embodiment 13

[0099] The difference between this comparative example and Example 1 is that the composition ratio of each component in the raw material of this example is as shown in Table 1, and the content ratio of La2O3 to HfO2 is 6.5:1, which is higher than the content ratio of La2O3 to HfO2 in Example 1. The remaining steps and parameters are the same as those in Example 1, and the detection indicators and methods are the same as those in Example 1.

[0100] Comparative Example 1

[0101] The difference between this comparative example and Example 1 is that the composition ratio of each component in the raw materials of this comparative example is as shown in Table 3, and the content of SiO2 in the batch material is 13% by mass percentage of oxides, which is significantly lower than the content of SiO2 in the example; B2O3 is 23%, which is significantly higher than the content of B2O3 in the example. The remaining steps and parameters are the same as those in Example 1, and the detection indexes and methods are the same as those in Example 1. The actual picture of the prepared microchannel plate microporous structure array is as follows Figure 2 shown.

[0102] Comparative Example 2

[0103] The difference between this comparative example and Example 1 is that the proportion of each component in the raw materials of this comparative example is as shown in Table 3, and the content of SiO2 in the batch material is 30% by mass percentage of oxides, which is significantly higher than the content of SiO2 in the example; Ho2O3 is 2%, which is significantly lower than the content of Ho2O3 in the example; and (SiO2+B2O3):(Ho2O3+HfO2) is 6.6:1, which is significantly higher than the ratio of (SiO2+B2O3) to (Ho2O3+HfO2) in the example. The remaining steps and parameters are the same as those in Example 1, and the detection indicators and methods are the same as those in Example 1.

[0104] Comparative Example 3

[0105] The difference between this comparative example and Example 1 is that the distribution ratio of each group in the raw materials of this comparative example is shown in Table 3, Ho2O3 is 15%, which is significantly lower than the Ho2O3 content in the example; and (SiO2+B2O3):(Ho2O3+HfO2) is 1.2:1, which is significantly lower than the ratio of (SiO2+B2O3) to (Ho2O3+HfO2) in the example. The remaining steps and parameters are the same as in Example 1, and the detection indicators and methods are the same as in Example 1.

[0106] Comparative Example 4

[0107] The difference between this comparative example and Example 1 is that the distribution ratio of each group in the raw materials of this comparative example is as shown in Table 3, and the sum of the contents of La2O3 and HfO2 is 36, which is higher than the sum of the contents of La2O3 and HfO2 in the example. The remaining steps and parameters are the same as those in Example 1, and the detection indicators and methods are the same as those in Example 1.

[0108] Comparative Example 5

[0109] The difference between this comparative example and Example 1 is that the preparation process is shown in Table 4. In the process of preparing the core glass rod, there is no rough annealing step, and precision annealing is directly used to obtain the core glass rod. The remaining steps and parameters are the same as those in Example 1, and the detection indicators and methods are the same as those in Example 1.

[0110] Comparative Example 6

[0111] The difference between this comparative example and Example 1 is that the preparation process is as shown in Table 4. In the process of preparing the core glass rod, during the rough annealing process, the annealing temperature is 800° C. and kept for 4 hours. During the precision annealing process, the temperature is raised to 500° C. and kept for 4 hours. The remaining steps and parameters are the same as those in Example 1, and the detection indicators and methods are the same as those in Example 1.

[0112] Comparative Example 7

[0113] The difference between this comparative example and Example 1 is that the preparation process is shown in Table 4. In the process of preparing the core glass rod, during the precision annealing process, the heating rate is 2.0°C / min, and the temperature is heated to 600°C and then kept for 6 hours. The remaining steps and parameters are the same as in Example 1, and the detection indicators and methods are the same as in Example 1.

[0114] In the following tables, Table 1 is the glass composition of each embodiment; Table 2 is the process conditions of each embodiment; Table 3 is the glass composition of each comparative example; Table 4 is the process conditions of each comparative example; Table 5 is the test results of the embodiments and the comparative examples.

[0115] Each component in Table 1 and Table 3 is the mass percentage of oxides, and the unit is %. In Table 1 and Table 3, m is the sum of the mass percentages of La2O3 and HfO2; m1 is the sum of the mass percentages of SiO2 and B2O3; m2 is the sum of the mass percentages of HfO2 and Ho2O3; and a is the mass ratio of La2O3 to HfO2.

[0116] In Table 2 and Table 4, T 熔 is the glass melting temperature, unit: °C; t 熔 is the glass melting time, unit: h; T 成is the glass forming temperature, unit ℃; T1 is the rough annealing temperature, unit ℃; t1 is the rough annealing time, unit h; α is the heating rate during precision annealing, unit ℃ / min; T2 is the precision annealing holding temperature, unit ℃; t2 is the precision annealing holding time, unit h; β is the precision annealing cooling rate, unit ℃ / min.

[0117] In Table 5, A represents the thermal expansion coefficient of the core glass at 300°C, in units of ×10 -7 / K; B represents the acid corrosion rate of the core glass, in mg / (cm 2 ×min); C represents the core material glass transition temperature T g , the unit is ℃; D represents the softening temperature of the core glass T f , the unit is ℃; E represents the anti-crystallization performance of the glass; F represents the shape of the micropores after acid etching when combined with the third-generation leather glass; - represents that the relevant data cannot be tested or has not been tested.

[0118] Table 1 Ratio of raw material components in each embodiment

[0119]

[0120] Table 2 Preparation process conditions of each embodiment

[0121]

[0122] Table 3 Glass component ratios of various comparative examples

[0123]

[0124]

[0125] Table 4 Preparation process conditions of each comparative example

[0126]

[0127] Table 5 Test results of embodiments and comparative examples

[0128]

[0129]

[0130] Combining the examples and the data in Tables 1, 2 and 5, it can be seen that the core glass for the microchannel plate prepared by the present invention has excellent performance, a high acid dissolution rate, and a transition temperature T g ≥700℃, softening temperature T f ≥760℃, thermal expansion coefficient 80~85×10 -7 / K; and the third generation microchannel plate with a high degree of matching with the skin material glass; and the microchannel plate prepared by using the core material glass for the microchannel plate prepared by the present invention and matching with the skin material glass for the third generation microchannel plate, the microchannel plate microporous structure formed after the acid etching process Figure 1 As shown, it is circular.

[0131] Furthermore, through the study of the examples, it is found that the core glass of the present invention has no crystallization and phase separation at 750-1100°C when the mass ratio of La2O3 to HfO2 in its glass components is 3-6:1, and has good anti-crystallization performance; the acid dissolution rate of the core glass sample is tested using 10% hydrochloric acid at 60°C, and the acid dissolution rate is ≥10mg / (cm 2 ×min). In the glass component of Example 12, when the content ratio of La2O3 and HfO2 is 1.9:1, which is not within the range of 3 to 6:1, the acid dissolution rate of the core glass is significantly reduced, which brings considerable difficulties to the acid etching through-hole process of the microchannel plate, and the success rate of preparing the corresponding microchannel plate is low. In the glass component of Example 13, the mass ratio of La2O3 and HfO2 is 6.5:1, which is not within the range of 3 to 6:1, resulting in poor anti-crystallization ability of the core glass, crystallization and phase separation during acid dissolution, and the stability of the prepared MCP is poorer than that of Examples 1-11. The reason is that La2O3 is a component that easily causes crystallization of glass during the mixing and cooling process, and HfO2 can weaken this trend. Therefore, it is necessary to ensure that the ratio of the two is within a certain range. Exceeding this range will easily lead to glass crystallization.

[0132] Furthermore, in the glass components of Comparative Example 1, since the content of SiO2 is less than 18% and the content of B2O3 is greater than 16%, the softening temperature of the prepared core glass is low and cannot be adapted to the third-generation microchannel plate skin glass, which results in the micropore shape of the prepared microchannel plate being as follows: Figure 2 As shown, it is a hexagonal shape, which does not meet the requirements for use of a microchannel plate.

[0133] Furthermore, in the glass component of Comparative Example 2, since the content of SiO2 is higher than 24% and the content of Ho2O3 is reduced to 2%, the mass ratio of (SiO2+B2O3) to (Ho2O3+HfO2) is not in the range of 1.5 to 3.5:1, resulting in a significant decrease in the softening temperature of the prepared core glass, and the shape of the micropores of the prepared microchannel plate is hexagonal, which does not meet the use requirements; at the same time, its anti-crystallization ability deteriorates.

[0134] Furthermore, in the glass component of Comparative Example 3, the mass percentage of Ho2O3 is increased to 15%, and the required clarification temperature during the melting process is significantly increased, resulting in a significant increase in the difficulty of melting; at the same time, since the mass ratio of (SiO2+B2O3) to (Ho2O3+HfO2) is not in the range of 1.5 to 3.5, the glass has poor anti-crystallization performance, and there is obvious crystallization during the drawing process, which makes it impossible to prepare the corresponding microchannel plate.

[0135] Furthermore, in the glass components of Comparative Example 4, the sum of the mass percentages of La2O3 and HfO2 is 36%, which is not within the range of 23-35%, resulting in poor chemical stability and structural stability, and poor anti-crystallization performance, which is not conducive to the forming, processing and storage of glass rods, and increases processing costs and usage risks. The reason is that: La2O3 and HfO2 are both glass exogenous oxides and cannot form glass alone. They are in the network exogenous position in the glass structure. If their content is too high, the glass network formed by silicon-oxygen tetrahedrons will be interrupted, making the glass structure loose, thereby reducing the stability of the glass.

[0136] Furthermore, in the process of preparing the core glass of Comparative Example 5, rough annealing was not performed, and precision annealing was directly adopted, resulting in damage to the MCP prepared therein during the cold working process and the acid etching process. The reason is that the lack of rough annealing resulted in residual stress, and the large internal stress will cause the glass to crack or break during subsequent processing and use. For example, during processing such as cutting, the stress concentrated area will suddenly crack, affecting the processing quality and causing safety hazards.

[0137] Furthermore, in the rough annealing process of the core glass in Comparative Example 6, the annealing temperature is kept at 800°C, and the temperature is increased to 500°C during the precision annealing process, causing it to lose its original shape stability and cause it to be severely deformed under its own gravity. At the same time, the internal microstructure of the core glass will also be destroyed. The reason is that the annealing temperature of the glass is higher than the softening temperature, the glass will gradually soften, and it is difficult to maintain its original shape.

[0138] Furthermore, in the precision annealing process of preparing the core glass of Comparative Example 7, the heating rate is 2.0°C / min and the cooling rate is 2.0°C / min, which leads to a decrease in the mechanical strength of the glass. In the subsequent processing and MCP preparation process, it is easy to break when subjected to a small external force impact and cannot be used normally. The reason is that the cooling rate is too fast, the shrinkage speeds of different parts of the glass are inconsistent, and a large internal stress is generated.

[0139] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0140] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A core glass for a microchannel plate, characterized in that: Calculated in terms of oxide mass percentage, it includes: 18-24% SiO2; 0-16% B2O3; the sum of La2O3 and HfO2 is 23-35%; 10-16% BaO; 1-4% Al2O3; 3-7% Y2O3; 5-10% Ho2O3; the sum of the contents of SiO2 and B2O3 is m1; the sum of the contents of HfO2 and Ho2O3 is m2; m1:m2 is 1.5-3.5:

1.

2. The core glass according to claim 1, characterized in that: The mass ratio of the La2O3 to the HfO2 is 3 to 6:

1.

3. The core glass according to claim 1, characterized in that: It also includes a fining agent, which is at least one of Sb2O3 and As2O3.

4. The core glass according to claim 3, characterized in that: The clarifier is 0.1-0.3%.

5. The core glass according to any one of claims 1 to 4, characterized in that: The core material glass transition temperature T g ≥700℃; softening temperature T f ≥760℃; thermal expansion coefficient at 20~300℃ is 80×10 -7 / K~85×10 -7 / K.

6. A method for preparing core glass for a microchannel plate, characterized in that: It contains the following steps: S1: The raw materials are mixed uniformly to form a batch material; the batch material comprises, in terms of oxide mass percentage, 18-24% SiO2; 0-16% B2O3; the sum of La2O3 and HfO2 is 23-35%; 10-16% BaO; 1-4% Al2O3; 3-7% Y2O3; 5-10% Ho2O3; the sum of the contents of SiO2 and B2O3 is m1; the sum of the contents of HfO2 and Ho2O3 is m2; m1:m2 is 1.5-3.5:1; S2: Melting, clarifying and homogenizing the batch material prepared in S1 to obtain glass liquid; S3: Cooling the glass liquid homogenized in S2 to 1300-1400°C, and then performing casting, rough annealing, and precision annealing in sequence to obtain a core glass rod; S4: Optically grind and polish the core glass rod prepared in S3.

7. The preparation method according to claim 6, characterized in that: The S2 melting temperature is 1400-1550° C., and the melting time is 6-8 hours.

8. The preparation method according to claim 6, characterized in that: During the rough annealing process, the annealing temperature is kept at 600-700° C. for 3-6 hours.

9. The preparation method according to claim 6, characterized in that: The precision annealing comprises: heating to 550-650° C. at 2.5-4.0° C. / min, keeping the temperature for 3-5 hours, and then cooling to room temperature at 0.5-1.5° C. / h.

10. A microchannel plate comprising a skin glass and a core glass, characterized in that: The core glass is the core glass according to any one of claims 1 to 5; the skin glass transition temperature T g ≥620℃, softening temperature T f ≥680℃, thermal expansion coefficient of 20~300℃ is 70×10 -7 / K~75×10 -7 / K.